Necessary condition for some singular stochastic control systems with variable delay - Nilgun, M.; Agayeva, Ch.A. (Інститут математики НАН України, 2008)
The purpose of this paper is to study conditions for the optimality of singular stochastic control systems with variable delay and constraint on the endpoint of state. The necessary condition of optimality for singular systems is obtained.